2022
DOI: 10.1038/s41531-022-00427-3
|View full text |Cite
|
Sign up to set email alerts
|

Treadmill training in Parkinson’s disease is underpinned by the interregional connectivity in cortical-subcortical network

Abstract: Treadmill training (TT) has been extensively used as an intervention to improve gait and mobility in patients with Parkinson’s disease (PD). Regional and global effects on brain activity could be induced through TT. Training effects can lead to a beneficial shift of interregional connectivity towards a physiological range. The current work investigates the effects of TT on brain activity and connectivity during walking and at rest by using both functional near-infrared spectroscopy and functional magnetic reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…Thus, we considered the inclusion of motion parameters regression, including WM and CSF, as adequate for this study. This regression approach has been widely utilized in fMRI connectivity studies in previous research ( Blasi et al, 2020 ; Fleischer et al, 2020 ; Diaz et al, 2021 ; Ding et al, 2022 ) and was found to better capture temporal degrees of freedom compared to other advanced artifacts removal methods ( Blasi et al, 2020 ). Finally, the time series extraction based on HMAT ( Archer et al, 2018 ) atlas was carried out.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we considered the inclusion of motion parameters regression, including WM and CSF, as adequate for this study. This regression approach has been widely utilized in fMRI connectivity studies in previous research ( Blasi et al, 2020 ; Fleischer et al, 2020 ; Diaz et al, 2021 ; Ding et al, 2022 ) and was found to better capture temporal degrees of freedom compared to other advanced artifacts removal methods ( Blasi et al, 2020 ). Finally, the time series extraction based on HMAT ( Archer et al, 2018 ) atlas was carried out.…”
Section: Methodsmentioning
confidence: 99%
“…Secondly, the BOLD signal is relatively slow, with changes occurring over several seconds, which is believed to be related to underlying neuronal activity and functional connectivity in the brain ( Fox and Raichle, 2007 ). The low-frequency range (0.009–0.08 Hz) has been used in numerous fMRI studies to investigate functional connectivity in the human brain ( Biswal et al, 1995 ; Fox et al, 2005 ; Fox and Raichle, 2007 ; Ding et al, 2022 ). Since the precise distribution of the MVAR coefficients is not known, we used a surrogate approach to check the significance of the results.…”
Section: Methodsmentioning
confidence: 99%
“…A small pilot study suggested that intensive treadmill training for 6 weeks improved motor symptoms and enhanced gait rhythmicity in PD (Herman et al, 2007). The therapeutic effect afforded by treadmill training may be facilitated via modifications in cerebellum activity (Maidan et al, 2017), reduced pre-frontal cortex activation (Thumm et al, 2018), and changes in interregional connectivity between cortical and subcortical brain regions (Ding et al, 2022). Tai Chi, sometimes described as "meditation in motion, " is a low-impact and slow-motion exercise with breathing control that has been shown to improve gait and balance in PD.…”
Section: Figurementioning
confidence: 99%